Global emissions of terpenoid VOCs from terrestrial vegetation in the last millennium. Issue 11 (9th June 2014) - Acosta Navarro, J. C.; Smolander, S.; Struthers, H.; Zorita, E.; Ekman, A. M. L.; Kaplan, J. O.; Guenther, A.; Arneth, A.; Riipinen, I.
Abstract We investigated the millennial variability (1000 A.D.–2000 A.D.) of global biogenic volatile organic compound (BVOC) emissions by using two independent numerical models: The Model of Emissions of Gases and Aerosols from Nature (MEGAN), for isoprene, monoterpene, and sesquiterpene, and Lund‐Potsdam‐Jena‐General Ecosystem Simulator (LPJ‐GUESS), for isoprene and monoterpenes. We found the millennial trends of global isoprene emissions to be mostly affected by land cover and atmospheric carbon dioxide changes, whereas monoterpene and sesquiterpene emission trends were dominated by temperature change. Isoprene emissions declined substantially in regions with large and rapid land cover change. In addition, isoprene emission sensitivity to drought proved to have significant short‐term global effects. By the end of the past millennium MEGAN isoprene emissions were 634 TgC yr−1 (13% and 19% less than during 1750–1850 and 1000–1200, respectively), and LPJ‐GUESS emissions were 323 TgC yr−1(15% and 20% less than during 1750–1850 and 1000–1200, respectively). Monoterpene emissions were 89 TgC yr−1(10% and 6% higher than during 1750–1850 and 1000–1200, respectively) in MEGAN, and 24 TgC yr−1 (2% higher and 5% less than during 1750–1850 and 1000–1200, respectively) in LPJ‐GUESS. MEGAN sesquiterpene emissions were 36 TgC yr−1(10% and 4% higher than during 1750–1850 and 1000–1200, respectively). Although both models capture similar emission trends, the magnitude of the emissions are different. This highlights the importance of building better constraints on VOC emissions from terrestrial vegetation.